2012
DOI: 10.1097/jom.0b013e3182619053
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Worksite Heart Health Improvement Project on Work Ability

Abstract: There was preliminary evidence that the WHHIP improved work ability, and future research should assess the impact of improved work ability on patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Thus solutions require not only physically healthier environments, such as hazard free workplaces, safe streets and access to fresh fruits and vegetable outlets, but also psychosocially healthier conditions that promote the empowerment of workers and community members and in which all individuals are treated fairly. For example, an intervention with nursing home workers used the SEF to design specific organizational practices and policies to support exercise and dietary improvements [Flannery, et al 2012]. …”
Section: Applying a Social Ecologic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus solutions require not only physically healthier environments, such as hazard free workplaces, safe streets and access to fresh fruits and vegetable outlets, but also psychosocially healthier conditions that promote the empowerment of workers and community members and in which all individuals are treated fairly. For example, an intervention with nursing home workers used the SEF to design specific organizational practices and policies to support exercise and dietary improvements [Flannery, et al 2012]. …”
Section: Applying a Social Ecologic Frameworkmentioning
confidence: 99%
“…Thus solutions require not only physically healthier environments, such as hazard free workplaces, safe streets and access to fresh fruits and vegetable outlets, but also psychosocially healthier conditions that promote the empowerment of workers and community members and in which all individuals are treated fairly. For example, an intervention with nursing home workers used the SEF to design specific organizational practices and policies to support exercise and dietary improvements [Flannery et al, 2012]. Community or society level influences include political, social, and economic forces that determine the kind of local industry and availability of good jobs, access to transportation, access to supermarkets and fresh food outlets, and housing options [Morland et al, 2006;Larson et al, 2009;Walker et al, 2010].…”
Section: Applying a Social Ecologic Frameworkmentioning
confidence: 99%
“…In addition, the study participants reported being too tired to engage in healthy behaviors, such as physical activity and heart healthy meal preparation, outside of work. This may be due to the demanding nature of their work, and/or because many NAs report working consecutively long shifts, mandatory overtime, and/or have second jobs (Flannery, Resnick, & McMullen, 2012). This reinforces the critically important need to incorporate health promotion activities into NAs' workday.…”
Section: Downloaded By [Massachusetts Prim Board] At 09:13 05 April 2015mentioning
confidence: 95%
“…Specifically, these studies reported that WHP programs resulted in decreased musculoskeletal symptoms (Dehlin, Berg, Hedenrud, Andersson, & Grimby, 1978;Härmä, Ilmarinen, Knauth, & Rutenfranz, 1988;Skargren & Oberg, 1996), improved muscle strength (Dehlin et al, 1978;Härmä et al, 1988;Skargren & Oberg, 1996), increased cardio-respiratory fitness (Härmä et al, 1988), decreased job strain (Dehlin et al, 1978), and reduced fatigue while at work (Härmä et al, 1988) . A recently published study testing WHP with NAs focused on reducing CVD and resulted in decreasing blood pressure and depressive symptoms while also improving lipid panels and work productivity (Flannery, Resnick, Galik, et al, 2012;Flannery, Resnick, & McMullen, 2012). Challenges associated with participation in these programs due to work-related responsibilities have been noted in prior research (Hess, Borg, & Rissel, 2011;Lemon et al, 2010;Skargren & Oberg, 1996).…”
mentioning
confidence: 99%
“…For improving or preserving future work ability, researchers seem -to a large extent -to rely on increasing physical fitness by means of exercise training (7) or improving cardiovascular risk factors (8). This led to varying results in the studies.…”
Section: Should Construction Workers Work Harder To Improve Their Heamentioning
confidence: 99%